Hand made houses for ex-Kamaiyas: a pattern language for the production of low-cost self-help housing in western Terai regions of Nepal - Bajracharya, Amit (Kansas State University, 2011)
Kamaiya is a system of Nepalese agriculture bonded labor. In typical wage labor, one can enter or withdraw from the labor market as an independent agent; in the case of bonded labor, however, a worker cannot control his or her labor power. The Kamaiyas were liberated by the Nepalese government in 2000, and promised land to build houses. Without enough money for construction, however, many of these “ex-Kamaiyas,” as they are now called, are without housing or live in sub-standard units. This thesis examines the housing possibilities for the ex-Kamaiyas and aims at creating basic guidelines for planning and designing low-cost, self-help housing. The thesis is an attempt to design affordable and environmentally responsive housing that draws on Nepalese vernacular traditions but incorporates some modern materials and construction methods. The research and designs are based on interviews with ex-Kamaiyas living in the Nepalese villages of Tesanpur, Janatanagar, and Bhuri Gaun. The thesis serves as a guide for non-profit organizations working to provide housing for the ex-Kamaiyas and consists of guidelines, termed “design patterns,” for laying out ex-Kamaiya neighborhoods and for designing and constructing individual houses. The thesis also provides step-by-step construction guidelines for building the houses. The thesis’s last chapter evaluates the proposed housing system and identifies strengths and weaknesses.
Keywords: Self-Help; Low-Cost; Housing; Ex-Kamaiyas; Architecture (0729); Area Planning and Development (0341)